The Publishing Game: The dubious mission of evaluating research and measuring performance in a cross-disciplinary field - Wagner, U. (Scandinavian Sport Studies Forum, 2016)
Sport is a cross-disciplinary research field in which, similar to other fields, the axiom publish or perish dominates. Despite differences in scientific publishing cultures, researchers of a cross-disciplinary spectrum like sport science are often subjected to a single performance measurement regime. By using Denmark as a case, this paper critically examines how scientific contributions are validated and evaluated, and subsequently how academic performance is measured and ranked in a cross-disciplinary research field. Drawing on critical realism, the claim is that the interplay between national performance indicators, multiple stakeholders and certain journals` editorial practices within the sport sciences undermine peer reviewing as our core procedure to ensure high academic quality standards. By emphasizing the fight for research autonomy and rather than rejecting peer reviewing per se, proposals for an extended reviewing practice and quality criteria that goes beyond ranking systems are suggested.